2021
DOI: 10.1177/15910199211025917
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastography (TEG) results are predictive of ischemic and hemorrhagic complications in patients with unruptured intracranial aneurysms treated with flow diversion

Abstract: Introduction Flow diversion is an effective treatment modality for intracranial aneurysms but is associated with ischemic and hemorrhagic complications. Patients treated with flow diversion require dual antiplatelet therapy and subsequent platelet function tests. At our institution, Thromboelastography with Platelet Mapping (TEG-PM) is the test of choice. The primary objective of this study was to identify TEG parameters that are predictive of postoperative complications in patients treated with elective flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…We acknowledge that platelet inhibition testing in the setting of flow diversion of intracranial aneurysms remains controversial, with questions regarding its efficacy, the best method of evaluating platelet inhibition levels (eg, light transmission platelet aggregation, thromboelastography (TEG)/platelet mapping system) as well as the optimum PRU range in centers using the VerifyNow assay. Yet, several prior investigations have now demonstrated an association between low VerifyNow PRU values and hemorrhagic complications following flow diversion 9–15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that platelet inhibition testing in the setting of flow diversion of intracranial aneurysms remains controversial, with questions regarding its efficacy, the best method of evaluating platelet inhibition levels (eg, light transmission platelet aggregation, thromboelastography (TEG)/platelet mapping system) as well as the optimum PRU range in centers using the VerifyNow assay. Yet, several prior investigations have now demonstrated an association between low VerifyNow PRU values and hemorrhagic complications following flow diversion 9–15…”
Section: Discussionmentioning
confidence: 99%
“…However, implantation of the flow diverter requires patients to be on antiplatelet therapy to prevent acute clotting, even for the newest version of PED with its thrombogenicity-reducing surface modification 6–8. Although controversial, multiple prior studies have now identified low and high levels of platelet inhibition to be associated with thromboembolic and hemorrhagic complications, respectively, during PED treatment 9–15. Consequently, based on the emerging literature, as well as our own experience, we have elected to strive to maintain a moderate level of platelet inhibition throughout the periprocedural period in flow diversion patients by titrating clopidogrel dosing based on the results of the VerifyNow P2Y12 platelet inhibition assay (Accumetrics, San Diego, California, USA).…”
Section: Introductionmentioning
confidence: 99%
“…TEG parameters showed an evitable role in improving hematological outcomes in people who underwent neurosurgeries whether they were adults [164][165][166][167][168] or children [169]. TEG parameters like TEG-R, TEG-MA, TEG-K, and TEG α-angle could predict hypercoagulation or thrombotic complications [164,166,168,169]; however, compared to control treatment, no difference was observed [170].…”
Section: Neurologicalmentioning
confidence: 99%
“…TEG parameters showed an evitable role in improving hematological outcomes in people who underwent neurosurgeries whether they were adults [164][165][166][167][168] or children [169]. TEG parameters like TEG-R, TEG-MA, TEG-K, and TEG α-angle could predict hypercoagulation or thrombotic complications [164,166,168,169]; however, compared to control treatment, no difference was observed [170]. In addition, these parameters predicted bleeding and hypo-coagulation status whether intraoperative or postoperative [166,169,171,172] besides using them could decrease bleeding complications risk compared to other conventional labs [170].…”
Section: Neurologicalmentioning
confidence: 99%
“…Loss of function genotypes for these alleles do not alter the pharmacodynamics of other P2Y12 inhibitors such as prasugrel or ticagrelor. There is an increasing body of evidence that suggests that the PRU as assessed by the VerifyNow P2Y12 assay—though sometimes limited by low platelet count or low hematocrit—is the most useful assay at predicting periprocedural hemorrhagic and thrombotic complications during FD placement, although thromboelastography may also be useful in predicting CNS ischemic and access site hemorrhagic complications 20–23…”
Section: Reversal Of Direct Oral Anticoagulantsmentioning
confidence: 99%